2023
DOI: 10.1098/rsos.221239
|View full text |Cite
|
Sign up to set email alerts
|

Walk the plank! Using mobile electroencephalography to investigate emotional lateralization of immersive fear in virtual reality

Abstract: Most studies on emotion processing induce emotions through images or films. However, this method lacks ecological validity, limiting generalization to real-life emotion processing. More realistic paradigms using virtual reality (VR) may be better suited to investigate authentic emotional states and their neuronal correlates. This pre-registered study examines the neuronal underpinnings of naturalistic fear, measured using mobile electroencephalography (EEG). Seventy-five healthy participants walked across a vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 98 publications
1
2
0
Order By: Relevance
“…The validity of corresponding mobile EEGs has already been described by Wascher et al (2021). Furthermore, the work of El Basbasse et al ( 2023), among others, has already confirmed that reliable data can be derived using mobile EEG recordings, including the implementation of the easyCap system, in conjunction with VR headsets [19,20]. The results of this study support this work.…”
Section: Objective Workloadsupporting
confidence: 85%
“…The validity of corresponding mobile EEGs has already been described by Wascher et al (2021). Furthermore, the work of El Basbasse et al ( 2023), among others, has already confirmed that reliable data can be derived using mobile EEG recordings, including the implementation of the easyCap system, in conjunction with VR headsets [19,20]. The results of this study support this work.…”
Section: Objective Workloadsupporting
confidence: 85%
“…Media outlets often use video recordings to report on criminal incidents, and the speed at which these videos are presented can influence viewers' perceptions and judgments. In general, slow motion in visual media was positively correlated with higher physiological arousal (Detenber et al, 2021;El Basbasse et al, 2023), and, in journalism, emotional arousal is frequently cited as a key component in eliciting negative emotional responses (Goutier, 2021). Furthermore, according to Roggenkamp (2005), nineteenth-century newspapers are characterized by their innovative nature, commercial focus, sensationalism, and, most notably, their emphasis on dramatic storytelling.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it is believed that different areas on different sides of the brain are responsible for formulating language, movements, emotion processing etc. [399,203,137,287,412,112].…”
Section: Brain Lateralizationmentioning
confidence: 99%